The concept of preventing negative consequences of work overload based on positive interactions between work and life, and promotion of workers' healthy behaviors - Agata Basinśka-Zych; Agnieszka Springer (The Central European Review of Economics and Management (CEREM), 2017)
Aim: The main aim of this article is to identify negative health consequences resulting from work overload and lack of work-life balance, as well as to present characteristics of positive healthy behaviors in the workplace as counteracting strategies. The paper is a part of the discussion on the concept of corporate wellness which forms the basis for the development of organization's health culture.Design / Research methods: The paper is based on a review of literature concerned with the factors influencing worker welfare. Moreover, it presents two case studies on comprehensive health programs implemented by Mars Poland and the Belgian branch of Protect & Gamble.Conclusions / findings: Based on the review of foreign and domestic literature, the authors propose a model describing the relationship between individual variables impacting worker welfare. In this model, it is assumed that the interaction between work and life, and workers' healthy behaviors such as physical activity and rest after work (sleep) are crucial to workers' regeneration.Originality / value of the article: The value of the paper lies in the interdisciplinary approach to the development of worker well-being. Apart from the perspective of human resources management, the outlined concept also takes into account the issues relating to workers' mental and physical health.Implications of the research: The theoretical assumptions presented in the paper will become a starting point for a research project to be conducted on Polish enterprises. Its objective will be to identify the possibilities of counteracting the negative effects of workload congestion through the promotion of healthy behaviors in the workplace and support of workers in their creation of a positive work-life interaction. – – Cel: Celem artykułu jest wskazanie negatywnych konsekwencji zdrowotnych wynikajacych zprzeciazėnia praca, braku roẃnowagi praca - dom (work-life balance), jak roẃniezċharakterystykapozytywnych zachowanṕrozdrowotnych w miejscu pracy jako formy przeciwdziałania im. Artykułwpisuje sie w dyskusje nad koncepcja corporate wellness, ktoŕa tworzy podstawy kultury zdrowotnejorganizacji.Metody badawcze: Praca opiera na sie na przegladzie literatury przedmiotu z zakresu czynnikoẃkształtujacych dobrostan pracownika. W artykule zaprezentowano takzė dwa studia przypadkoẃ wzakresie kompleksowych programoẃ zdrowotnych, realizowanych w spoĺce Mars Polska oraz wbelgijskim oddziale Procter & GambleWnioski: Bazujac na przegladzie literatury zagranicznej i krajowej, autorki proponuja koncepcjemodelowa opisujaca zalezṅosći pomiedzy poszczegoĺnymi zmiennym majacymi wpływ na dobrostanpracownika. W niniejszym modelu zakłada sie, zė dla powyzṡzej regeneracji pracownika kluczowa roleodgrywacb́edzie interakcja praca - dom oraz podejmowane przez pracownika zachowaniaprozdrowotne, takie jak aktywnosćf́izyczna i wypoczynek w formie snu.Wartosćártykułu: Wartosćártykułu zwiazana jest z interdyscyplinarnym podejsćiem dokształtowania dobrostanu pracownika. W prezentowanej koncepcji oproćz perspektywy zarzadzaniazasobami ludzkimi uwzgledniono roẃniezṗroblematyke zdrowia psychicznego i fizycznegopracownika.Implikacje badan\': Załozėnia teoretyczne przedstawione w artykule stana sie punktem wyjsćia doprojektowanych badanẃ polskich przedsiebiorstwach. Celem tych badanb́edzie identyfikacjamozl̇iwosći przeciwdziałania negatywnym skutkom przeciazėnia praca poprzez promocje zachowanṕrozdrowotnych w miejscu zatrudnienia oraz wspieranie pracownika w budowaniu pozytywnejinterakcji praca - zẏcie.
Keywords: M54; I12; M54; I12; 330; work overload; worker well-being; work-life balance; healthy behaviors; workplace health promotion; workplace health program; enterprises; corporate wellness